KUALITAS PELAYANAN JASA KONVENSI BAGI WISATAWAN KONVENSI PADA HOTEL DI KAWASAN PARIWISATA NUSA DUA, BALI - Dewi Hendriyani, I Gusti Ayu (JURNAL KEPARIWISATAAN, 2011)
Quality of service is dynamic condition that is related to service that fullfils or exceeds expectation. In the tourism sector, especially MICE, quality of service becomes success parameter. The aim of this research is, therefore, to investigate the service quality of convention activities at five star hotel in Nusa Dua Tourism Area, Bali. The factors that were observed are tangibles factor (eight variables), assurance factors (four variabels), reliability factors (four variables), emphaty factors (four variables), and responsiveness factors (four variables). The result of the study showed that the service quality of convention activities at five-star hotel in Nusa Dua Tourism area, Bali was good in owerall. The leading factor and variabel are assurance (F4) and the services are as guest expectation (Xi 8). The strategic implication was that the management of the hotels need to maintain the factors receiving good and improve the ones that was unfavourable.